Multifunctional Nanotheranostic Agent for NIR‐II Imaging‐Guided Synergetic Photothermal/Photodynamic Therapy. Issue 3 (28th December 2020) - Li, Tuanwei; Liu, Le; Xu, Pengping; Yuan, Pan; Tian, Youliang; Cheng, Quan; Yan, Lifeng
Abstract: All‐in‐one phototheranostics triggered by near‐infrared (NIR) light are receiving significant attention. Herein, an NIR (NIR‐I) probe with intrinsic multifunctionality is synthesized and encapsulated by an amphiphilic polypeptide P(OEGMA)21 ‐P(Asp)16 . The as‐fabricated polymeric micelles (P@BDP) serve as an NIR‐II imaging‐guided nanotheranostic platform for NIR‐I photothermal therapy (PTT) and photodynamic therapy (PDT). The P@BDP exhibit excellent photostability and equally outstanding photothermal conversion efficiency upon irradiation with a 730 nm laser (40.1%) or 808 nm laser (42.0%), yet significantly superior reactive oxygen species production capability under 730 nm laser irradiation. In vivo studies reveal that the capillary vessel of the mouse can be unambiguously detected and the accumulation of P@BDP in tumors can be monitored in real‐time by NIR‐II fluorescence imaging. Synergistic phototherapy (730 nm) can provide a highly desirable therapeutic effect under NIR‐II imaging‐guided PTT/PDT combination therapy. Abstract : A boron‐dipyrromethene‐based small‐molecule NIR‐I probe is synthesized and encapsulated by an amphiphilic polypeptide as a therapeutic nanoagent for photothermal therapy(PTT) under 808 nm laser irradiation or photodynamic therapy (PDT)/PTT combination therapy under 730 nm laser irradiation.